The prefix de- with applicative value. Study of pereo and depereo in the corpus of Plautus - González Saavedra , Berta (Cuadernos de Filología Clásica. Estudios Latinos, 2023)
In some cases, The preverbization of Latin verbs involves semantic and syntactic changes that have not been systematically explained, for example, when derivation implies transitivisation. By means of a comparative study of the preverbed verbs pereo (derived from eo) and depereo (derived from pereo), I will try to show how the study of this phenomenon applying the concept of applicative constructions can serve to illuminate this process. Telicity, which has been the most important factor in explaining this change in verbal semantics and verb argument structure, is not useful in the case of this pair, since the first, pereo, is telic, while the second, depereo, is not. Threfore, I will try to identify other factors that determine the change in the functioning of the derivative, such as the animacy of the elements that enter into the argument structure and the topicality.